2022
DOI: 10.1155/2022/5318117
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Aqueous Extract of Leaves and Seeds of Datura metel (Solanaceae) in Frog’s Heart Failure Model

Abstract: Objective. The aim of this work was to evaluate the antioxidant potential of Datura metel. Materials and Methods. Heart failure was induced in the frog’s heart by continuous perfusion of hydrogen peroxide. Survival time and some heart tissue parameters of oxidative stress were recorded in the presence of aqueous extracts of the leaves and seeds of Datura metel. Ascorbic acid was used as a reference drug. Results. H2O2-enriched Ringer’s solution inhibited the negative inotropic and chronotropic effects of acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Importantly, compared with other species like D. stramonium, D. metel’s antioxidant property is quite high ( Iqbal et al, 2017 ). Antioxidant action is estimated by the aqueous extract of seed and leaf of D. metel at 2.5 and 1.5 mg/mL, respectively; they also found that it prolongs the cardiac arrest to 35 to 37 min, when the heart's normal survival time is 14 min ( Mbida et al, 2022 ). Four extract concentrations of four different solvents of D. metel extract 25–100 mg/mL were investigated in DPPH scavenging activity, total phenolic content, the reducing power assay, hydroxyl-radical scavenging, and β-carotene bleaching test.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, compared with other species like D. stramonium, D. metel’s antioxidant property is quite high ( Iqbal et al, 2017 ). Antioxidant action is estimated by the aqueous extract of seed and leaf of D. metel at 2.5 and 1.5 mg/mL, respectively; they also found that it prolongs the cardiac arrest to 35 to 37 min, when the heart's normal survival time is 14 min ( Mbida et al, 2022 ). Four extract concentrations of four different solvents of D. metel extract 25–100 mg/mL were investigated in DPPH scavenging activity, total phenolic content, the reducing power assay, hydroxyl-radical scavenging, and β-carotene bleaching test.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by the administration of Leaves and Seeds of D. metel increased levels of superoxide dismutase, glutathione peroxidase, and catalase in Frog’s Heart Failure Model. 30 …”
Section: Discussionmentioning
confidence: 99%
“…As above mentioned, "hairy" root lines can be valuable not only due to high antioxidant activity, but due to exceptional reducing power as well. Most methods of reducing power evaluation are based on the ability of plant extracts to reduce radicals and metals [10][11][12][13][14][15][16][17]. DPPH (2,2-diphenyl-1picrylhydrazyl), ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) and NO (nitric oxide) tests are the most common in the first group, and FRAP (ferric reducing antioxidant power), FTC (ferric thiocyanate) and CUPRAC (cupric ions reducing assay) methods in the second.…”
Section: Introductionmentioning
confidence: 99%